Effects of strength training on Olympic time-based sport performance: A systematic review and meta-analysis of randomized controlled trials - Lum, D.; Barbosa, T. M. (International Journal of Sports Physiology and Performance, 2019)
The main aim of this study was to systematically review the current body of knowledge on the effects of strength training on OTBS time-trial performance (ie, endurance running, cycling, swimming and rowing). The second aim was to conduct a meta-analysis providing an estimate of the contributions by several factors to the improvement in OTBS time-trial performance (such as age, training status, and duration of training program).